2018
DOI: 10.1021/acs.langmuir.8b00458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oil Hydrophobicity on the Adsorption and Rheology of β-Lactoglobulin at Oil–Water Interfaces

Abstract: The adsorption of protein layers at oil-water interfaces is critical to the formation and stability of various emulsions in, for example, technical applications as well as in biological lipid storage. Effects of ionic strength, pH, temperature, and pretreatments of the proteins are well-known. However, the oil phase has been regarded as exchangeable and its role in protein adsorption has been widely ignored. Herein, the influence of systematically selected oil interfaces of high purity on the formation and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 38 publications
7
57
2
Order By: Relevance
“…Similar results were also observed in a previous work by Sakuno, Matsumoto, Kawai, Taihei, and Matsumura (), where they compared the adsorption behaviors and structural changes of β ‑lactoglobulin at the DAG–water interface and TAG–water interface, and found that a larger concentration of proteins was adsorbed to the TAG–water interface with a higher degree of structure unfolding. In a recent work using a model O/W emulsion, it has been reported that an increase in oil polarity delayed the adsorption and denaturation of proteins, thus leading to slower formation of interfacial film with decreased mechanical strength (Figure 3c; Bergfreund et al., ), which can largely explain the above‐mentioned results when DAG oils are used as the oil phase in contrast to TAGs.…”
Section: Physicochemical Properties Of Slsmentioning
confidence: 88%
See 3 more Smart Citations
“…Similar results were also observed in a previous work by Sakuno, Matsumoto, Kawai, Taihei, and Matsumura (), where they compared the adsorption behaviors and structural changes of β ‑lactoglobulin at the DAG–water interface and TAG–water interface, and found that a larger concentration of proteins was adsorbed to the TAG–water interface with a higher degree of structure unfolding. In a recent work using a model O/W emulsion, it has been reported that an increase in oil polarity delayed the adsorption and denaturation of proteins, thus leading to slower formation of interfacial film with decreased mechanical strength (Figure 3c; Bergfreund et al., ), which can largely explain the above‐mentioned results when DAG oils are used as the oil phase in contrast to TAGs.…”
Section: Physicochemical Properties Of Slsmentioning
confidence: 88%
“…(a) The impact of addition of different concentrations of MAG or DAG on the interfacial tension of stripped soybean oil (SSO) (Chen et al., ); (b) The interfacial tension versus time for the 1 wt% sodium caseinate solution in the presence of peanut oil (PO) or peanut oil‐based diacylglycerol (PO‐DAG) (Long et al., ); (c) Schematic illustration of the effect of oil polarity on adsorption of β ‐lactoglobulin and interfacial film structure at oil–water interface in a model system (Bergfreund et al., ); (d) Microscopy images of oil foams formed by air bubbles dispersed in sunflower oil stabilized by MAGs: (left) cryo‐scanning electron microscopy (SEM) image, (middle) CLSM image, and (right) polarized light image (Heymans et al., )…”
Section: Physicochemical Properties Of Slsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethanol is chosen as a spreading agent as it is known to have no short-term effects on BLG amyloid fibrils. 1,22 Hexane is also known to have no significant effects on BLG proteins, 23 thus constituting an appropriate choice for the non-polar phase. Using a Hamilton 10 ml microsyringe, the desired quantity of mixture is deposited directly at the interface and left to equilibrate for 10 minutes.…”
mentioning
confidence: 99%